Odpowiedzi

2009-11-22T13:30:24+01:00
1.(x +5z)(b-11)=xb-11x+5zb-55z
2.(a-6b)(-8 -13b)=-8a+13ab+48b+78b²
3.(a - 4b)(2b - 7a)=2ab-7a²-8b²+28ab=-7a²-8b²+3ab
4.(x+2+y)(z+1)=xz+z+2z+3+yz+y
5.(a+b)(7-b+4c)=7a+ab+4ac+7b+b²+4c
6.(p-2s+5t)(5p-3)=5p²-3p310ps+6s+25pt-15t

pozdrawiam Nala.;p
2009-11-22T17:41:53+01:00
1. (x +5z)(b-11) = bx-11x+5bz-55z
2. (a-6b)(-8 -13b) = -8a-13ab+48b+78b2
3. (a - 4b)(2b - 7a) = 2ab-7a2-8b2+28ab = 30ab-7a2-8b2
4. (x+2+y)(z+1) = xz+x+2z+2+yz+y
5. (a+b)(7-b+4c) = 7a-ab+4ac+7b-b2+4bc
6. (p-2s+5t)(5p-3) = 5p2-3p-10ps+6s+25pt-15t